Makna Dakwah dalam Lirik Lagu “Eling-Eling Umat”: Analisis Deskriptif terhadap Representasi Ketundukan dan Keutamaan Salat dalam Media Musik Populer - Firmansyah, Asep; Gunawan, Muhammad (FASTABIQ: JURNAL STUDI ISLAM, 2025)
This study examines the da‘wah messages embedded in the song “Eling-Eling Umat” by Ebith Beat A, focusing on how its lyrics promote the obligation of ṣalāh and cultivate spiritual awareness among listeners. Using a qualitative descriptive-analytical approach, this research draws on document analysis grounded in the theory of fiqh al-ṣalāh and da‘wah through creative media. The findings indicate that the song conveys explicit messages regarding the mandatory nature of ṣalāh and implicit messages related to its spiritual virtues and the consequences of negligence. The lyrics integrate normative religious teachings with creative da‘wah strategies expressed through popular musical forms, enabling broader public engagement. The study concludes that popular religious music can function as an effective medium for strengthening awareness of ṣalāh and for enhancing the community’s spiritual connection to Islamic values.Keywords: Ṣalāh; da‘wah; religious music; Ebith Beat A; fiqh of ṣalāh; popular culture.